Cognitive behavioral therapy for insomnia combined with eszopiclone for the treatment of sleep disorder patients transferred out of the intensive care unit: A single-centred retrospective observational study. Issue 37 (September 2018) - Zhang, Ying; Su, Jun; Wang, Jingquan; Tang, Guangzhang; Hu, Wei; Mao, Jinghong; Ren, Wanwen; Liu, Yi; Yu, Zhenghe
Abstract : Abstract: Patients transferred out of the intensive care unit (ICU) are always impaired by sleep disorders. Cognitive behavioral therapy for insomnia (CBT-I) and eszopiclone are 2 commonly prescribed strategies for insomnia. In the current study, the effect of the combined application of the 2 methods on sleep disorders in ICU transferred out patients was assessed. Twenty-nine insomnia patients receiving combined treatment of CBT-I and eszopiclone and a corresponding number of patients treated with eszopiclone were collected. The incidence of discomfort experiences in ICU was recorded. Polysomnogram (PSG), Pittsburgh Sleep Quality Index (PSQI), self-rating anxiety scale (SAS), self-rating depression scale (SDS), and treatment emergent symptom scale (TESS) were used to assess the treatment efficacy and side effects. Hospitalization for over 7 days, use of benzodiazepines, and experiencing anxiety, insomnia, and mechanical ventilation increased chances of sleep disorders. The sleep latency, awakening time, and total sleep time were further improved in patients treated with the combined therapy than patients treated with eszopiclone ( t = −2.334, −2.412, 2.383, P < .05). Similar changing pattern was observed for PSQI score ( t = −2.262, P < .05). The improvement effect of the combined therapy on the sleep efficacy, SWS phase III, and rapid eye movement sleep was also significantly stronger ( t = 2.112, 2.268, 2.311, P < .05). Moreover, the SAS and SDS scores in patients treated with the combined therapy decreased more than those of patients treated with eszopiclone. The efficacy of CBT-I combined with eszopiclone in the treatment of sleep disorders in ICU transferred out patients was better than eszopiclone.